Hepatoprotective Saikosaponin Homologs from Comastoma pedunculatum - Cui, Bao-Song; Qiao, Yong-Qi; Yuan, Yi; Tang, Li; Chen, Hui; Li, Yan; Li, Shuai (Planta Medica, 2014)
Eight new triterpenoid saponins, the saikosaponin homologs comastomasaponins A–H (1–8), as well as a known triterpenoid (9) and eight known saponins (10–17) were isolated from the aerial portions of Comastoma pedunculatum. The structures of these compounds were elucidated spectroscopically, and their hepatoprotective activity and cytotoxic activity were evaluated against five human tumor cell lines in vitro. Compounds 1, 5–12, 14, 15, and 17 exhibited potent hepatoprotective activity, and compound 11 displayed cytotoxic activity against HCT-8, Bel-7402, BGC-825, A549, and A2780 human tumor cell lines.
Keywords: Gentianaceae; Comastoma pedunculatum; saikosaponin homologs; hepatoprotective activity; cytotoxic activity